The Influence of Transformational Leadership and Organizational Culture on the Performance of Employees of the Regional Public Company Service Unit (Perumda) Tirta Musi Palembang with Work Motivation as an Intervening Variable - Septia Rizki Mutiara; Badia Perizade; Yuliani Syapril (International Journal of Social Service and Research, 2023)
This study aims to determine the direct effect of transformational leadership and organizational culture on employee performance, the indirect effect of transformational leadership and organizational culture on employee performance through the work motivation of the Perumda Tirta Musi Palembang service unit. Respondents in this study were taken using a census. The total population for filling out the questionnaire is 305 respondents. The data analysis technique used is the Structural Equation Model (SEM). The results of this study indicate that transformational leadership has a direct positive effect on performance, organizational culture has a direct positive effect on performance, transformational leadership has a positive effect on work motivation, organizational culture has a positive effect on work motivation, work motivation has an effect on performance, transformational leadership has a positive effect on performance through motivation, organizational culture influences performance through motivation as an intervening variable. This proves that work motivation is a good intervening variable or intermediary variable for transformational leadership on performance, and organizational culture on performance. This means that transformational leadership affects the level of employee motivation so that it can affect employee performance so that it can improve performance.